Lake-Level Changes and Their Paleo-Climatic Implications at the MIS12 Lower Paleolithic (Middle Pleistocene) Site Marathousa 1, Greece - Bludau, Ines J. E.; Papadopoulou, Penelope; Iliopoulos, George; Weiss, Max; Schnabel, Ellen; Thompson, Nicholas; Tourloukis, Vangelis; Zachow, Charlotte; Kyrikou, Styliani; Konidaris, George E.; Karkanas, Panagiotis; Panagopoulou, Eleni; et al. (Frontiers in Earth Science, 2021)
Lithics and cut-marked mammal bones, excavated from the paleo-lake Marathousa 1 (MAR-1) sediments in the Megalopolis Basin, southern Greece, indicate traces of hominin activity occurring along a paleo-shoreline 444,000 years (444 ka) ago. However, the local environment and climatic conditions promoting hominin activity in the area during the MIS12 glacial remain largely unknown. In order to reconstruct the paleo-environment including paleo-lake levels and governing paleo-climatic factors on a high temporal resolution, we analyzed a 6-meter-long sediment sequence from the archeological site MAR-1. A multiproxy approach was applied using ostracods, sponge spicules, diatoms, grain sizes, total organic carbon, total inorganic carbon and conventional X-ray fluorescence analysis. The results from the site represent a protected region surrounded by high mountains under the constant influence of water, either as a shallow partly anoxic water body surrounded by reed belts (>463–457 ka, <434–427 ka), a riverine-lake deltaic system (~457–448 ka), a floodplain (~448–444 ka) or a seasonal freshwater pond (~444–436 ka). The local changes of water levels resemble large trends and rhythms of regional records from the Mediterranean and appear to directly respond to sea surface temperature (SST) changes of the North Atlantic. In particular, when the SSTs are high, more moisture reaches the study area and vice versa. Additional water reaches MAR-1 through melting of the surrounding glaciers after brief warm phases during MIS12 in the Mediterranean realm, which leads to the formation of smaller fresh water ponds, where also the horizon of the excavated remains is placed. Such ponds, rich in ostracods and other microorganisms, provided mammals and humans valuable resources, such as potable water, a wide range of plant species and hunting opportunities, thus bear a high archaeological potential. The results from our study suggest that the Megalopolis Basin could have served as a refugium for hominins and other organisms due to its capacity to retain freshwater bodies during glacial and interglacial periods.